Properties of wire+ arc additively manufactured 2024 aluminum alloy with different solution treatment temperature - Qi, Zewu; Cong, Baoqiang; Qi, Bojin; Ding, Jialuo (Elsevier, 2018)
2024 aluminum alloy deposits were produced with wire + arc additive manufacturing procedure. Solution treatment + natural aging processes with different solution treatment temperature were conducted to improve the properties. The microstructure and mechanical properties were investigated. After heat treatment the distributing characteristic of the second phase changed to be dispersive from continuous in as-deposited condition. Solution treatment + natural aging process can significantly improve the properties of WAAM 2024 aluminum alloy. With higher solution treatment temperature, the micro hardness, tensile properties and elongation presented an increasing trend. After 503 °C solution treatment + natural aging process, the micro hardness, ultimate tensile strength, yield strength and elongation were 143HV, 497 MPa, 330 MPa and 16%, respectively, which can nearly meet the applying requirement.
Keywords: Wire + arc additive manufacturing; Solution treatment temperature; Metals and alloys; Mechanical property; Microstructure